Can Restorative Justice provide a solution to the problem of incoherence in sentencing? - TIARKS, ELIZABETH,JANE (2016)
Current sentencing practice in England and Wales is incoherent. This stems from the combination of conflicting philosophies of punishment, with no clear method adopted by sentencers in choosing between them. This presents a significant challenge as sentencing can have a profound impact on an offender’s life, as well as having wider implications for family members. Therefore, a coherent decision-making process is essential in order to limit arbitrary sentencing and support the legitimacy of the penal system. This thesis argues that Restorative Justice might offer a more coherent decision-making process. Restorative Justice is hypothesised to operate as a kind of mediation process between the philosophies of punishment and understandings of justice held by participants. Their voluntarily agreed outcome should therefore represent the best possible compromise between participants’ ideas of justice and philosophies of punishment. Analysis of existing empirical research has been undertaken, involving the examination of existing studies of Restorative Justice in Northern Ireland, England and Wales, Australia and New Zealand. This empirical research has explored problems which can arise in practice for the theoretical conception of Restorative Justice as a mediation process between ideas. The thesis concludes that Restorative Justice can in theory offer a more coherent process of sentencing, but that there are a number of obstacles to realising this in practice